2017
DOI: 10.1002/bdr2.1053
|View full text |Cite
|
Sign up to set email alerts
|

Hypomethylation and decreased expression of BRG1 in the myocardium of patients with congenital heart disease

Abstract: These results suggested that the early high expression of BRG1 in fetal hearts maintained normal cardiac development and that the abnormal hypomethylation and decreased expression of BRG1 in human hearts probably affect the expression of GATA4, which affects the pathogenesis of CHD. Birth Defects Research 109:1183-1195, 2017. © 2017 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…The current study represents a genome-wide methylation analysis of relatively complicated cardiac defects. Previous DNA methylation studies were limited to analyses of methylation status in some congenital heart defect candidate genes (10,11,(21)(22)(23), and were insufficient to reveal information for DNA methylation on a global scale. One previous study conducted a genome-wide DNA methylation study (24) and found more hypermethylated than hypomethylated DMRs in myocardial samples from pediatric patients with CHDs compared with controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study represents a genome-wide methylation analysis of relatively complicated cardiac defects. Previous DNA methylation studies were limited to analyses of methylation status in some congenital heart defect candidate genes (10,11,(21)(22)(23), and were insufficient to reveal information for DNA methylation on a global scale. One previous study conducted a genome-wide DNA methylation study (24) and found more hypermethylated than hypomethylated DMRs in myocardial samples from pediatric patients with CHDs compared with controls.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in heart tissue samples from patients 1-48 months in age, decreased whole-genome methylation levels, implied by analyzing long interspersed nucleotide element (LINE)1 methylation status, was associated with increased risk of tetralogy of fallot (TOF) ( 9 ). Changes in DNA methylation at the promoter and intron regions of several heart development-related genes, including NK2 homeobox 5, GATA binding protein 4, heart and neural crest derivatives expressed 1, and SWI/SNF-related matrix associated actin-dependent regulator of chromatin subfamily a member 4, and their association with the expression of these genes, have also been reported in the myocardium of children with ventricular septal defect (VSD), TOF, and double-chambered right ventricle ( 10 , 11 ). However, limited studies have examined DNA methylation during the fetal period, a key stage when cardiac structures are forming.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the down-regulation of BRG1 gene expression at birth was also observed in normal human hearts. However, unlike in adult mouse hearts where the BRG1 was undetectable in cardiomyocytes, it remains detectable in human adult cardiomyocytes, suggesting the other mechanisms may be present in regulating the switch of fetal and adult MHC in humans (50). Nevertheless, in hypertrophic and failing hearts, the subunits of BAF complexes and its binding partners, HDACs and PARPs, were increased and the expression of fetal MHC was up-regulated, whereas the adult MHC was decreased (46).…”
Section: Atp-dependent Chromatin Conformation Remodeling and Hfmentioning
confidence: 95%
“…Studies have shown that there are hypermethylation of myocardial-related genes in myocardial tissues of CHD, which is closely related to gene downregulation [4,5]. In patients with CHD, decreased transcriptional activity of CITE2, ZIC3, NR2F2 and BRG1 is associated with abnormal methylation [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%